1988
DOI: 10.1111/j.1749-6632.1988.tb22319.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation in Cancer Cells: Chemical and Physical Studies a

Abstract: Our studies on the biochemical composition and the structural organization of smooth and rough endoplasmic reticulum isolated from Morris hepatomas 9618A and 3924A confirm the results obtained employing the total microsomal fraction. We have definitely established the following facts: (1) Tumor subcellular organelles exhibit the very low degree of peroxidizability that has been shown to be related to the growth rate of the tumor. (2) Associated with such a low susceptibility to peroxidation are (a) changed lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…9-Hydroxystearic acid (9-HSA) belongs to the class of endogenous lipid peroxidation by-products that are greatly diminished in tumors and therefore become unable to exert their normal controlling functions on cell division (1). Indeed, in HT29 cells, exogenous administration of 9-HSA at micromolar concentrations results in a significant inhibition of proliferation rate as well as a significant increase of p53-independent p21 WAF1 expression (2).…”
mentioning
confidence: 99%
“…9-Hydroxystearic acid (9-HSA) belongs to the class of endogenous lipid peroxidation by-products that are greatly diminished in tumors and therefore become unable to exert their normal controlling functions on cell division (1). Indeed, in HT29 cells, exogenous administration of 9-HSA at micromolar concentrations results in a significant inhibition of proliferation rate as well as a significant increase of p53-independent p21 WAF1 expression (2).…”
mentioning
confidence: 99%
“…Growing evidence points to the involvement of long‐chain lipid peroxidation by‐products in the control of cell proliferation and tumour growth. Previous studies have shown that the endogenous production of two hydroxy derivatives of linoleic and arachidonic acids was greatly diminished in experimental hepatomas compared to control tissue, and was related to the cellular prooxidant/antioxidant balance, the proliferative status, and the grade of differentiation of the tumours 1. The investigation was then extended to cell lines, trying to identify new endogenous oxidation products of biological interest.…”
mentioning
confidence: 99%
“…In fact, the observed decrease of oxidizable lipids in hepatocyte nodules (Figs. 6, 7) is likely the result of their consumption during previous LPO Schaur et al 1987;Masotti et al 1988b). Thus, the lower inducibility of lipid oxidatin by H202 plus iron(II) in hepatocyte nodules can be interpreted as a further indication, besides the loss of protein thiols, of an ongoing lip- Altogether, the data reported in the present study point to the possibility that a process of LPO takes place continuously in vivo during chemical hepatocarcinogenesis, with a strict localization at the GGT-rich areas of chemically transformed cells.…”
Section: Discussionmentioning
confidence: 99%